2018
DOI: 10.3847/1538-4357/aab6ad
|View full text |Cite
|
Sign up to set email alerts
|

Electron Heating in Low Mach Number Perpendicular Shocks. II. Dependence on the Pre-shock Conditions

Abstract: Recent X-ray observations of merger shocks in galaxy clusters have shown that the post-shock plasma is two-temperature, with the protons being hotter than the electrons. In this work, the second of a series, we investigate by means of two-dimensional particle-in-cell simulations the efficiency of electron irreversible heating in perpendicular low Mach number shocks. We consider values of plasma beta (ratio of thermal and magnetic pressures) in the range 4 β p0 32 and sonic Mach number (ratio of shock speed to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 39 publications
5
29
0
Order By: Relevance
“…The reason for this is that there is heating at the shock front, due to both compression and entropy generation. Both processes could affect electrons and ions differently, resulting in a downstream plasma with different electron and ion temperatures (Guo, Sironi & Narayan 2017, 2018). In a pair plasma, electrons and positrons will undergo identical heating, so we can speak of a single perpendicular temperature and a single parallel temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is that there is heating at the shock front, due to both compression and entropy generation. Both processes could affect electrons and ions differently, resulting in a downstream plasma with different electron and ion temperatures (Guo, Sironi & Narayan 2017, 2018). In a pair plasma, electrons and positrons will undergo identical heating, so we can speak of a single perpendicular temperature and a single parallel temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This choice was motivated by two reasons: the temperature of the two species would have the same value downstream of the shock and the instabilities, relevant for this problem, are unchanged in the electron-positron limit (Gary & Karimabadi 2009;Schlickeiser 2010). In the ion-electron limit, the temperature of the two species is not necessarily equal (Guo et al 2017(Guo et al , 2018Tran & Sironi 2020), however, examining this problem in this framework would require a description of the ion/electron energy partition. While this is an important step in understanding the physics of non-relativistic collisionless shocks, it is beyond the scope of this work The setup of the shock simulations are similar to those described in Spitkovsky (2008b); Sironi & Spitkovsky (2011b); Sironi et al (2013), where the shock is formed by initializing the plasma with a supersonic flow towards a reflecting wall (in the negative 𝑥 direction) on the left hand side of the simulation.…”
Section: Simulationsmentioning
confidence: 99%
“…However, some theoretical studies of collisionless shocks showed that shocks primarily heat ions. Guo et al (2018) carried out two-dimensional kinetic particle-in-cell simulations of low-Mach-number shocks, assuming galactic shocks, and showed T e /T i ∼ 0.24 at M = 5, independent of the plasma beta ranging 4 < β < 32. In addition, Matsukiyo (2010) found that the post-shock temperature ratio is proportional to the magnetosonic Mach number and T e /T i = 0.01 when the shock parameters are β = 10 and M = 14.…”
Section: Electron Heating At Shock Wavesmentioning
confidence: 99%